Measuring STEM engagement among middle school children involved in educational robotics: a narrative review - Monica Pivetti; Virginia Dusi (Discover Education)
Abstract Student engagement has been considered an antecedent of school achievement and a protective factor against school dropout. Some concerns have been raised concerning its under-theorization, that is the inadequate theoretical discourse about the meaning and nature of student engagement. Also, educational robotics (ER) has been found to increase students’ learning motivation as well as students’ learning outcomes. While a growing number of studies has investigated the role of ER in the development of STEM engagement, the way this concept is defined and measured among young children is poorly investigated. This narrative review attempts to bridge this methodological gap by surveying the ways STEM engagement has been measured among middle school children involved in ER activities. The definition of “engagement” in STEM education is blurry and its borders often overlap with other concepts such as attitudes, motivation and self-efficacy. This dimension has been measured via validated questionnaires and non-validated measures among middle school children. As for non-validated measures, the items investigated (a) interest towards STEM subjects; (b) interest towards STEM-related career; (c) self-efficacy. As for the validated scale, two instruments have been used: (a) Student Attitudes Toward Science, Technology, Engineering and Math survey (S-STEM); (b) STEM Career Interest Survey (STEM-CIS).